Implementasi Prinsip Komunikasi Islam dalam Khutbah Jumat - Saputra, Wahidin; Kusmiati, Yopi (Journal of Islamic Communication Studies, 2026)
This study is grounded in the strategic role of Friday sermons (khutbah Jumat) as a medium of Islamic preaching that not only conveys religious messages but also shapes the attitudes and behaviors of congregants through effective and ethical communication. The study aims to examine the implementation of Islamic communication principles in Friday sermons, particularly the practices of ‘qaulan sadidan’, ‘qaulan layyinan’, and ‘qaulan ma'rufan’, at Assalam Mosque of the Ministry of Public Works of the Republic of Indonesia in 2025. This research employed a qualitative approach using a case study method. Data were collected through direct observation of Friday sermon activities, in-depth interviews with the sermon preacher (khatib) and congregants, and document analysis of sermon manuscripts. The data were analyzed through data reduction, data display, and conclusion drawing, while triangulation was employed to ensure the trustworthiness of the findings. The results reveal that the principle of ‘qaulan sadidan’ is reflected in the delivery of factual, truthful, and scripturally grounded messages; ‘qaulan layyinan’ is manifested through the use of polite, persuasive, and non-confrontational language; while ‘qaulan ma'rufan’ is implemented through the selection of expressions that are socially appropriate and responsive to the characteristics of the congregation. These three principles complement one another in fostering effective Islamic communication and positively influencing the congregants' religious understanding and awareness. This study contributes to the advancement of Islamic communication studies, particularly in the discourse on Islamic preaching rhetoric within public religious spaces.